u2-9u+8=0

Simple and best practice solution for u2-9u+8=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u2-9u+8=0 equation:



u2-9u+8=0
We add all the numbers together, and all the variables
u^2-9u+8=0
a = 1; b = -9; c = +8;
Δ = b2-4ac
Δ = -92-4·1·8
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-7}{2*1}=\frac{2}{2} =1 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+7}{2*1}=\frac{16}{2} =8 $

See similar equations:

| x2+6=x3-2 | | 4g/3=2 | | 7/8t=8/9 | | d/3-5=13 | | -3x+5=6x-14 | | 20=3(2x+1)+7x | | 8n+3/15=15/n | | (x-15)-(2x-10)=2 | | 8x+3=15/8x | | 6x+2(x–3)=4x+x–18 | | x-x^-12=0 | | 2(4z–9–11)=166–46 | | x-√x-12=0 | | 6y+10=53 | | 8n+3=15/8n | | m+4=12=9 | | 8n+3/15=8n | | 8n+3/15=n | | Y+11÷6-x+1÷9=x+7÷4 | | 8n+3=15/n | | 3x^2-100=143 | | 8n+3=15n | | Y+11÷6-y+1÷9=y+7÷4 | | x(x-13)(x+1)=0 | | (3x+4)-(7x-3)=10 | | x0.6=1.2 | | 5/x-5=-4/x+4+9/(x-5)(x+4) | | -16+(m/4)=-3 | | 3^x+2+4*3^x+1=21 | | 5y2+27y+28=0 | | 12:4=x:4 | | -16+(x•-4)=-3 |

Equations solver categories